Pengaruh Strategi Merek, Identitas Visual, dan Riset Pasar terhadap Ekuitas Merek melalui Persepsi Konsumen pada PT Solusi Teknologi Aplikasi Yasha di Jakarta Selatan - Akil, Rendy Elriza; Zaharuddin, Zaharuddin; Kusuma, Sitta (Jurnal EMT KITA, 2026)
This study aims to determine and analyze the influence of Brand Strategy, Visual Identity, and Market Research on Brand Equity through Consumer Perception at PT Yasha Application Technology Solutions in South Jakarta. This study uses a quantitative approach. The research population is 100 consumers of PT Yasha Application Technology Solutions in South Jakarta. The sampling technique used is Simple Random Sampling, so the sample used in this study is 100 respondents. The data collection techniques used in this study are distributing questionnaires and observation. The analysis technique used in this study is the SPSS version 20 program. The results of the study indicate that there is no significant influence between the Visual Identity Brand Strategy variable (X1) on Consumer Perception (M) at PT Yasha Application Technology Solutions in South Jakarta. There is a significant influence between the Market Research variable (X2) on Consumer Perception (M) at PT Yasha Application Technology Solutions in South Jakarta. There is a significant influence between the Consumer Perception variable (M) on Brand Equity (Y) at PT Yasha Application Technology Solutions in South Jakarta. This shows that Brand Strategy, Visual Identity (X1), Market Research (X2), and Consumer Perception (M) simultaneously have a significant influence on Brand Equity (Y).